"That's Just What You Do": Applying the Techniques of Neutralization to College Hazing. Issue 10 (3rd October 2021) - Alexander, Kellie; Opsal, Tara
ABSTRACT: Hazing is a prevalent behavior on college campuses that is harmful and can be dangerous, yet remains understudied in sociological literature. While research demonstrates that a majority of undergraduate students who are members of clubs, teams, and organizations experience hazing during college, over half of these students do not consider themselves to have been hazed, indicating a gap between how students experience and understand hazing. To understand this disjuncture, we conducted qualitative interviews with undergraduate students who belong to college organizations where research demonstrates hazing may occur: fraternities, sororities, club sports teams, ROTC, and marching band. Our research findings indicate that participants draw on "techniques of neutralization" to excuse or justify hazing which helps create a university "hazing culture" whereby these behaviors become normalized and pervasive, making university programmatic interventions particularly challenging. Based on our findings, we make recommendations for universities and policymakers who are increasingly integrating anti-hazing programming and policies to address the culture of hazing on U.S. college campuses.